Vitreo-retinal disorders at high altitude in Nepal - Thapa, R; Paudyal, G; Crandall, AS; Tabin, G (Nepalese Journal of Ophthalmology, 2013)
Introduction: Nepal has many mountains including the highest one in the world. People living in high altitude are often involved in climbing mountains. Objective: To explore the pattern of vitreo-retinal disorders at high altitude in Nepal. Materials and methods: Consecutive patients aged 40 years and older who presented at the micro-surgical eye camp at Lukla of Solukhumbu district (2,860 metres) were included. Detailed ocular and systemic histories and ocular examination including dilated fundus evaluation were done. Results: There were a total 81 patients with the mean age of 56.7 years (S.D 11.15). Females (51.9 %) outnumbered males. Sherpa comprised of 76.5 % followed by Rai (9.8 %). The main occupation was agriculture (51.9 %) followed by mountain trekking (28.4 %). Smokers comprised of 13.5 %. Hypertension was the predominant systemic problem (28 %). The best corrected visual acuity of 6/18 and better was found in 86.4 % of cases and less than 3/ 60 in 3.6 % of cases. Age-related macular degeneration (AMD) was found in 19.6 % of cases with a predominant mild AMD (16 %), hypertensive retinopathy in 12.2 %, with grade I hypertensive change in 8.6 %, retinal vein occlusion (RVO) in 7.1 % of cases and with a branch RVO in 4.9 %. Dilated and tortuous retinal vessels were present in 25.9 % of cases; out of this, 9.8 % of the cases had concurrent AMD and/or hypertensive retinopathy. Other retinal problems were macular hole (2.46 %), solar retinopathy (2.46 %) and choroidal tear (1.2 %). Conclusion: AMD, hypertensive retinopathy, and RVO are the main vitreo-retinal disorders besides the dilated and tortuous retinal vessels in people living at high altitude in Nepal. Nepal J Ophthalmol 2013; 5(9):57-62 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7823